Peripheral Blood Mesenchymal Stem Cells Isolated from Indonesia Long Tailed Monkey (Macaca fascicularis) - Agus Harsoyo; Dondin Sajuthi; Arief Boediono; Yoga Yuniadi; Irma H Suparto (Acta VETERINARIA Indonesiana, 2018)
An experiment to compare age of Macaca fascicularis (Mf) as pheripheral blood (PB) mesenchymal stem cell (MSC) isolate sources and the impact of its concentration on the pheriperal blood mononucleous cells (PBMC) development has been conducted. Twelve male Mf were used in this experiment. Three different age groups (infant (A1), juvenil (A2) and adult (A3)) of the Mfs were compared as treatments. Isolate of pheriperal blood MSC were created by taking 1 ml, 5 ml or 10 ml the Mfs pheriperal blood, processed them into PBMC, counted, isolated, cultured, subcultured, pelleted, extracted for their messenger Ribonucleic Acid (mRNA). Reverse transcriptase - polymerase chain reaction (RT-PCR) were conducted to obtain complentary Deoxyribonucleic Acid (cDNA). PCR amplification were performed to look cluster differentiation (CD) of the MSC gene expression. Incomplete block design was used and the data were analysed using descriptive statistic and T-Test. The results showed that PBMC counted from infant, juvenil and adult were 6.78 – 7.28, 6.18 – 7.30, and 6.01 – 7.34 log cell, respectively. The subculture and pelleting cells were only obtained from A3 with positive 73, 90, 105 and negative 34, 45 CD markers. It is concluded that pheriperal blood of adult Mf can be utilized as MSC source.